Decreased Serum Adipose Triglyceride Lipase Level Is Associated With Renal Function Impairment in Patients With Type 2 Diabetes - Ying Wang; Tongtong Liu; Nan Li; Tingting Zhao; Xiai Wu; Yanmei Wang; Xi Dong; Hailing Zhao; Weijing Liu; Ping Li (Journal of Diabetes Research)
Conclusion: Serum ATGL levels are linked to reduced renal function in T2DM patients. A decline in ATGL levels corresponded with a nonlinear rise in UACR and a drop in eGFR, suggesting that serum ATGL may serve as a potential biomarker for DKD development.